Reintroducing Macroeconomics : a Critical Approach. - Cohn, Steven Mark (Taylor and Francis, 2015)
This lively introduction to heterodox economics provides a balanced critique of the standard introductory macroeconomic curriculum. In clear and accessible prose, it explains many of the key principles that underlie a variety of alternative theoretical perspectives (including institutionalist economics, radical economics, Post Keynesian economics, feminist economics, ecological economics, Marxist economics, social economics, and socioeconomics). Because the book's structure parallels the chapters and subject matter presented in a typical introductory macroeconomics textbook, ""Reintroducing Ma.